Pharmaceuticals in Water - Raja, M. K. Mohan Maruga; Kathiravan, M. K. (Pharmaceuticals in Water, 2021)
The surface of the earth is covered with about 71% of water. Water constitutes 50 to 70% weight of the entire plants and animals, including humans. The physical and chemical changes of water happen either due to the human activities and/or the natural factors. The increasing usage of prescribed pharmaceuticals estimates that, by end of 2020, the global need would reach 4500 billion doses. The pharmaceuticals after consumption are excreted from the human body in their parent form or as metabolites and conjugate forms. Some of the widely used drugs or active pharmaceutical ingredients (APIs) are detected in various water resources and found to affect the quality of aquatic life species. The impact of the discharge of the pharmaceuticals into aquatic streams in a definite range is unlikely to elicit acute toxicity and their existence also affects the human health as well as agriculture and marine culture. The most relevant approach to decrease the presence of pharmaceuticals in water bodies is to avoid and/or decrease their entry into the water environment. This reduction could be attained through combined preventive measures through specific regulatory bodies which includes enhanced communication to the public on rational drug use and proper disposal of pharmaceuticals.